2018
DOI: 10.1111/jen.12499
|View full text |Cite
|
Sign up to set email alerts
|

Transportability of non‐target arthropod field data for the use in environmental risk assessment of genetically modified maize in Northern Mexico

Abstract: In country, non-target arthropod (NTA) field evaluations are required to comply with the regulatory process for cultivation of genetically modified (GM) maize in Mexico. Two sets of field trials, Experimental Phase and Pilot Phase, were conducted to identify any potential harm of insect-protected and glyphosate-tolerant maize (MON-89Ø34-3 × MON-88Ø17-3 and MON-89Ø34-3 × MON-ØØ6Ø3-6) and glyphosatetolerant maize (MON-ØØ6Ø3-6) to local NTAs compared to conventional maize. NTA abundance data were collected at 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…The results in this study showed no significant differences on the composition, species richness ( S ), Shannon–Wiener diversity index ( H′ ), evenness index ( J ), Simpson’s dominant concentration ( C ), community similarity and ecosystem functioning composition of the NTAs community between transgenic insect-resistant maize (SK12-5 transgenic Cry1Ab/2Aj ) and the non-GE maize. These results are consistent with previous studies showing that Bt maize producing Cry1Ab [ 18 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], Cry1Ab and Cry2Ab [ 45 ], Cry1A.105 and Cry2Ab [ 46 , 47 ], Cry1Ac [ 48 , 49 , 50 ], Cry1A.105 and Cry2Ab and Cry3Bb [ 51 ], Cry1Ab and Cry1Ac [ 52 ], Cry1Ab and VIP3A [ 53 ], Cry1F [ 54 , 55 , 56 ], Cry1Ah [ 57 ], Cry1Ie [ 58 , 59 , 60 ], Cry34Ab1 and Cry35Ab1 [ 55 , 61 ], Cry34Ab1 and Cry35Ab1 and Cry1F [ 55 , 61 ], Cry3Bb [ 62 , 63 , 64 , 65 ] and VIP 3A [ 66 ] insecticidal proteins did not affect populations of NTAs in the field. Similarly, there were no significant effects detected in the majority of such filed experiments with Bt cotton and Bt rice [ 37 , 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results in this study showed no significant differences on the composition, species richness ( S ), Shannon–Wiener diversity index ( H′ ), evenness index ( J ), Simpson’s dominant concentration ( C ), community similarity and ecosystem functioning composition of the NTAs community between transgenic insect-resistant maize (SK12-5 transgenic Cry1Ab/2Aj ) and the non-GE maize. These results are consistent with previous studies showing that Bt maize producing Cry1Ab [ 18 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], Cry1Ab and Cry2Ab [ 45 ], Cry1A.105 and Cry2Ab [ 46 , 47 ], Cry1Ac [ 48 , 49 , 50 ], Cry1A.105 and Cry2Ab and Cry3Bb [ 51 ], Cry1Ab and Cry1Ac [ 52 ], Cry1Ab and VIP3A [ 53 ], Cry1F [ 54 , 55 , 56 ], Cry1Ah [ 57 ], Cry1Ie [ 58 , 59 , 60 ], Cry34Ab1 and Cry35Ab1 [ 55 , 61 ], Cry34Ab1 and Cry35Ab1 and Cry1F [ 55 , 61 ], Cry3Bb [ 62 , 63 , 64 , 65 ] and VIP 3A [ 66 ] insecticidal proteins did not affect populations of NTAs in the field. Similarly, there were no significant effects detected in the majority of such filed experiments with Bt cotton and Bt rice [ 37 , 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…The food, feed, and environmental safety of GM maize, as well as their benefits to society, have been demonstrated by global cultivation and consumption of GM maize for over two decades and by studies that showed phenotypic, ecological, and compositional equivalence of GM and conventional crops (Corrales et al 2018; Phipps and Park 2002; Horak et al 2007; Drury et al 2008; Harrigan et al 2009; Ridley et al 2011; Sammons et al 2014; Nakai et al 2015; Horak et al 2015a, b; ISAAA 2016; Heredia-Diaz et al 2016). However, in spite of food, feed, and environmental safety record of GM crops, there remains some hesitation to accepting biotechnology products (ISAAA 2016) and questions have been raised regarding the potential impact that commercial cultivation of GM crops might have in regions where native landraces are traditionally grown by farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Only if a specific risk hypothesis is identified for a particular receiving environment, that cannot be addressed by the available information, local CFTs might be required to generate new information. There is published evidence supporting transportability of data generated in different geographies for the ERA of transgenic soybean and maize ( Horak et al, 2015 ; Nakai et al, 2015 ; Ahmad et al, 2016 ; Heredia Díaz et al, 2017 ; Corrales Madrid et al, 2018 ; Clawson et al, 2019 ; Matsushita et al, 2020 ). These publications show that, even when climate and production practices may be different, the environmental safety conclusions from the comparative assessments are consistent across geographies provided that studies are run across a broad range of conditions.…”
Section: Considerations For Transportability Of Conclusionmentioning
confidence: 86%
“…Based on the premise that “studies conducted in different countries may be relevant and can help risk assessors in making informed safety decisions” ( Garcia-Alonso et al, 2014 ), recent reports support transportability showing that environmental safety conclusions from comparative assessments are consistent across geographies ( Horak et al, 2015 ; Nakai et al, 2015 ; Ahmad et al, 2016 ; Heredia Díaz et al, 2017 ; Corrales Madrid et al, 2018 ; Clawson et al, 2019 ; Matsushita et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation